BELAJAR ISLAM MELALUI LITERATUR VISUAL: PEMBENTUKAN IDENTITAS MODERAT ANAK MUSLIM MILENIAL - Kirana Nur Lyansari (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
Moslem children have tended to learn religious teaching through teachers at the Taman Pendidikan Al-Qur’an (TPA) and Boarding School. Through the old religious authority, a teacher or cleric provided Islamic teaching taken from the classic books. However, in this millennial era, the old religious authorities must be collaborated with alternative kinds of literature, such as popular Islamic children books. This paper would like to see the presence of Islamic children's visual literature over the past few years as an alternative source of religious authority by analyzing the visual images and text displayed. The generation of millennial Muslim children consumes practical, interesting, and fun religious knowledge through Islamic visual literacy. The visual literature of the Islamic children in this paper includes three domains of analysis, namely: theology, daily ethics, and Sirah nabi. This paper argues that the presence of Islamic children's visual literature is as a media response in promoting polite preaching among millennial generation, as well as constructing alternative religious authority as a source of creating a new identity.